University Student Vulnerability to Phishing in Digital Banking across Social Platforms - Fitrah, Mutia Salsanu; Ramadhani, Sri; Syakir, Ahmad (Journal of Social Commerce, 2025)
Human fallibility to phishing is not the byproduct of ignorance anymore, but the one kept alive by the very structure of digital existence. The aesthetic of deception finds a fertile ground in the repetitiveness of trust, the aesthetic of familiarity, and fluid choreography of the communication process that occurs via a platform. The current paper investigates the effect that can be observed in students of Indonesian universities who, due to their exposure to mobile banking and messaging culture, do not regard phishing as a perversion but as something that may appear to be reality. The research, which is based on in-depth interviews, baffles the conclusion that deception is not triumphing with tricky technical challenges rather with social engineering that hopscotches through interpersonal pathways, uses institutional jargon, and play with emotional instinct. Subjects were not blind to the danger. They are weak, instead, because of the same set of circumstances that conditions them to act quickly, to accept as true signals that are visually consistent, and to place the value of the urgent ahead of checking. This evidence means that the issue is not the absence of awareness but the weakness of awareness in the face of pressure. Therefore, there is a need to change the way the digital vulnerability is thought of. Security should not be a personal issue that creates a vacuum out of a context. Rather, it needs to be regarded as a social/infrastructural question, one that is informed by design, by platform logic, by the relational predilections by which we characterize our everyday digital practice.